2008
DOI: 10.1074/jbc.m804858200
|View full text |Cite
|
Sign up to set email alerts
|

A Rotor-Stator Cross-link in the F1-ATPase Blocks the Rate-limiting Step of Rotational Catalysis

Abstract: The F 0 F 1 -ATP synthase couples the functions of H ؉ transport and ATP synthesis/hydrolysis through the efficient transmission of energy mediated by rotation of the centrally located ␥, ⑀, and c subunits. To understand the ␥ subunit role in the catalytic mechanism, we previously determined the partial rate constants and devised a minimal kinetic model for the rotational hydrolytic mode of the F 1 -ATPase enzyme that uniquely fits the pre-steady state and steady state data (Baylis Scanlon, J. A., Al-Shawi, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
3
14
0
Order By: Relevance
“…6B. The rate constants for each step are found in Scanlon et al (22,23). With the enzyme in V max conditions, we only observe the pauses at the 120°positions (32).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…6B. The rate constants for each step are found in Scanlon et al (22,23). With the enzyme in V max conditions, we only observe the pauses at the 120°positions (32).…”
Section: Discussionmentioning
confidence: 91%
“…Pre-steady state analysis of the burst kinetics of ATP hydrolysis at nearly V max conditions demonstrated that the rate-limiting transition state occurs after the reversible hydrolysis/synthesis step and before release of phosphate (P i ) (22,23). The rate-limiting step is likely associated with a rotation step because a ␥-␤ cross-linked enzyme is still able to undergo the initial ATP hydrolysis, but the rotation-impeded enzyme is unable to release P i (23). Significantly, the kinetics of steady state hydrolysis can only be assessed when the Mg⅐ATP concentration is high enough to fill all three catalytic sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the sequence of the four active site conformations considered here is most likely β TP → β DP → β HC → β E toward direction of hydrolysis (12,25), we conclude that III TS and II TS are most likely somewhat separated in time by the conformational changes of the active site. We notice that hydrolysis of ATP takes place after an approximately 90°substep of the γ-subunit (10) and P i release also takes place following an approximately 90°γ-subunit substep (10,20). In view of our current results, it thus seems logical that, in a selected active site, ATP hydrolysis and P i release require two separate 90°γ-subunit steps or, in other words, during the 2-ms waiting dwells these occur approximately in synchrony, but in different active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the function of the ATP synthase, structure determinations (12)(13)(14)(15)(16), mutation studies on the α-, β-, and γ-subunits (1,(17)(18)(19)(20), single-molecule studies (6,7,10), and simulations (11,(21)(22)(23)(24)(25)(26)(27)) have contributed to a rather detailed understanding of its mode of mechanical action. However, one of several issues that need to be better characterized (1) is the mechanistic resolution of the chemical reaction steps on the way from ADP to ATP at an atomic level.…”
mentioning
confidence: 99%